The Influence of Location on The Decision to Choose a Private University in Bali: The Mediation Effect of Brand Image - Wijaya, I Gusti Ngurah Satria; Nirmala , Annisa Rizky; Aldora, Putu Febby (LPPM Undiksha, 2024)
Higher education is a source of innovation and solutions for the growth and development of the nation along with the times. One of the critical issues of higher education is the decline in the number of new students entering private universities (PTS) influenced by the COVID-19 pandemic and the change of several State Universities to Legal Entity State Universities. This causes competition between PTS to be tighter and unavoidable. This study aims to analyze the location of private university selection decisions with the brand image variable as the mediating variable. The subjects of this study amounted to 200 students. The data in this study were collected using a questionnaire method with an instrument in the form of a questionnaire sheet. The analysis technique used in this research is structural equation model (SEM) analysis. This study's results indicate a significant influence between brand image and private college decisions. So it can be concluded that, partially, location and brand image have a positive and significant effect on the decision to choose a private university, and the area has a positive and significant impact on the brand image of private universities. As for the indirect effect, brand image can partially mediate the considerable influence of location on private college selection decisions. This research can guide the government and higher education managers in designing policies that support the availability of quality education in various places, thereby opening more comprehensive access for students to choose universities according to their needs and values.